Brand Credibility and Purchase Intention Among Users of Shopping and Convenience Goods: The Moderating Role of Brand Involvement - N., Joji Alex; Thomas, Jithin (Indian Journal of Marketing, 2014)
In the present study, we explore the moderating role of brand involvement, which is a potential factor influencing the relation between brand credibility and brand purchase intention. The study is intended for two categories of products, that is, convenience products and shopping products. The product being shopping in nature, the brand credibility (BC) and purchase intention (PI) scores are relatively higher and significant for two categories (high and low) of brand involvement (BI), depicting the complexity and importance shown by consumers while shopping for high ticket shopping goods. The product being convenience in nature, the brand credibility and purchase intention scores are relatively low and insignificant for the category of low brand involvement (<2.79), depicting the even lesser importance shown by consumers for convenience goods with lesser price points. At the same time, the brand credibility and purchase intention scores are relatively high and significant for the category of soap users with high brand involvement (>=2.79), depicting the importance shown by consumers of high end soaps with higher price points, even though they are convenience goods. In future studies, more categories of products like specialty products (e.g. luxury cars, deluxe vacations) and unsought products (e.g. life insurance and retirement plans) can be included to draw a detailed comparison across the consumer product classification.